Pemberian Ekstrak Bunga Telang (Clitoria Ternatea L) Menurunkan Stres Oksidatif dan Meningkatkan Berat Badan pada Tikus Wistar Jantan Diabetes: Administrations of Butterfly Pea Flower (Clitoria Ternatea L) Extract Reduce Oxidative Stress and Increase Body Weight of Male Wistar Rats with Diabetes - Tantri Febriana Putri; Brian Wasita; Dono Indarto (Amerta Nutrition, 2023)
Background: Asian pigeonwings flower (Clitoria Ternatea L.) is a plant that contains high antioxidants. Numerous research studies have shown that CT flowers can reduce the blood glucose levels of diabetic rats. Lower blood glucose levels can reduce MDA in DM patients. Objectives: This study aimed to analyze the effect of CT on serum malondialdehyde (MDA) levels and body weight of diabetic rats. Methods: Male albino Wistar rats induced by streptozotocin 45 mg/kgBW and nicotinamide 110 mg/kgBW to generate type 2 diabetes. Diabetes rats were randomly divided into three groups:  T1 was the control of diabetic rats, T2 was given 300 mg/kgBW extract of CT, and T3 was given 600 mg/kgBW extract of CT for 21 days. Data collected before, during, and after treatment were analyzed using One Way ANOVA and LSD posthoc. Results: The mean of MDA in the T2 and T3 groups decreased on day 14 that was T2 4,67±0,17 µmol/l and T3 3,99±0,30 µmol/l, (p<0,001) and on day 21 also decreased that was T2 4,07±0,14 µmol/l and T3 3,34 ±0,23 µmol/l (p<0,001). While T1 did not experience a significant decrease. The mean of body weight in the T2 and T3 groups increased on day 14 that was T2 187,83±4,67 grams and T3 183,50±4,41 grams (p<0,001), and on day 21, also increased was T2 195,17±3,65 grams, 190,67±4,08 grams (<0,001). In contrast, T1 did not experience a significant increase. Conclusion: Administration of CT flower extract 300 mg/KgBW, and CT flower extract 600 mg/KgBW reduces serum MDA levels of diabetic rats compared to the control of diabetic rats.